2022
DOI: 10.1007/s43032-022-00983-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Underweight and Obesity Are Associated with Placental Pathologies in Human Pregnancy

Abstract: Introduction: Maternal underweight and obesity are prevalent conditions, associated with chronic, low-grade inflammation, poor fetal development, and long-term adverse outcomes for the child. The placenta senses and adapts to the pregnancy environment in an effort to support optimal fetal development. However, the mechanisms driving these adaptations, and the resulting placental phenotypes, are poorly understood. We hypothesised that maternal underweight and obesity would be associated with increased prevalenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Secondly, being underweight may reflect the nutritional status of pregnant women, and malnutrition could weaken the immune system, thereby increasing sensitivity to environmental pollutants[ 33 ]. Additionally, the BMI of underweight individuals could intensify lung deposition and retention of particles [ 34 ]. Further research is warranted to delve deeper into the mechanisms underlying these associations, ultimately paving the way for informed strategies to mitigate the risks posed by prenatal air pollution exposure on maternal and fetal health.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, being underweight may reflect the nutritional status of pregnant women, and malnutrition could weaken the immune system, thereby increasing sensitivity to environmental pollutants[ 33 ]. Additionally, the BMI of underweight individuals could intensify lung deposition and retention of particles [ 34 ]. Further research is warranted to delve deeper into the mechanisms underlying these associations, ultimately paving the way for informed strategies to mitigate the risks posed by prenatal air pollution exposure on maternal and fetal health.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the placenta has a large impact on fetal development and placenta-related adverse pregnancy outcomes can influence later life disease. Placental function can be influenced by many environmental exposures, such as maternal smoking and obesity ( Reijnders et al, 2019 ; Scott et al, 2022 ). Increased physical activity before and during early pregnancy can reduce the incidence of preeclampsia ( Aune et al, 2014 ).…”
Section: Placenta-specific Effects Of Environment On Healthmentioning
confidence: 99%
“…(15)(16)(17)(18) Variable histopathological changes have also been reported in placentas of women with obesity, including both delayed and accelerated villous maturation, maternal vascular lesions, and chronic villitis. (15)(16)(17)(18)(19) Some of these studies cite small sample sizes, while others have a study design that is limited to term gestation, which could explain the mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, fetal sex is also known to affect adaptive changes in the placenta in response to altered maternal/uterine environment, including obesity, and has also been associated, not just with adverse pregnancy/neonatal outcomes, but also with speci c placental pathologies. (11,(19)(20)(21) As part of a large institutional effort to identify underlying causes of pregnancy complications, we previously conducted a study to evaluate placental pathology in the setting of maternal obesity, focusing on patients delivering at or near term. (22) This study found maternal obesity to be associated with large placental disc weight for gestational age and decreased placental e ciency, histopathologic lesions of chronic in ammation (speci cally chronic villitis [CV]) and fetal vascular malperfusion (FVM), and intrauterine fetal stress as manifested by normoblastemia, independent of diabetes and hypertension.…”
Section: Introductionmentioning
confidence: 99%